Performance enhancement mechanisms and optimization of multi-pass parallel flow condensers with liquid-vapor separation - Jin Huan Pu; Nan Hua; Xiaodong Jian; Ying Chen; Yongliang Li; Tong Yang; Hua Sheng Wang (Case Studies in Thermal Engineering)
This study employed a distributed-parameter model developed by the authors to investigate the mechanisms of condensation heat transfer enhancement using liquid-vapor separation (LS) in multi-pass parallel flow condensers (MPFCs). Additionally, tube pass arrangements for MPFCs with LS were optimized. Simulations characterized relationships among refrigerant flow rate, vapor quality, flow patterns, heat-transfer coefficient and pressure drop at tube level, along with heat-transfer coefficient and tube-wall temperature distributions at the segment level. An entropy analysis based on the second law of thermodynamics quantified contributions from heat transfer and pressure drop. The results demonstrate that introducing LS leads to (1) a 9.1 % increase in the average heat-transfer coefficient, (2) a 50.4 % reduction in pressure drop, (3) similar entropy generation numbers due to heat transfer for both MPFC and MPFC-LS, (4) significantly higher entropy generation numbers due to pressure drop in the last two tube passes, and (5) a 51.4 % lower average entropy generation number for MPFC-LS compared to MPFC. Compared to a baseline serpentine condenser, MPFCs-LS reduced pressure drop by 84 %–98 % while maintaining nearly the same heat transfer rate, resulting in an overall performance improvement of 5 %–9 %. The optimal tube-pass arrangement for MPFCs-LS was identified as 3-3-2-2-2-2-2-1-1-1-1.